Up-regulated BCAR4 contributes to proliferation and migration of cervical cancer cells. (June 2018) - Zou, Ruanmin; Chen, Xiangjian; Jin, Xuejing; Li, Shi; Ou, Rongying; Xue, Jisen; Yan, Xiaojian; Chen, Lulu; Hu, Yan; Zhu, Hua
Abstract: OBJECTIVES: Recently, thousands of long non-coding RNAs (lncRNAs) involved in development and metastasis of malignant tumors have been identified. Long non-coding RNA (lncRNA) breast cancer anti-estrogen resistance 4 (BCAR4) has been proved to promote proliferation and metastasis in multiple tumors. However, the function and significance of BCAR4 in cervical cancer are still unclear. METHODS: In this study, we concentrated on the biological function and clinical significance of BCAR4 in cervical cancer. More specifically, BCAR4 expression was evaluated in cervical cancer tissues and cell lines by qRT-PCR. Moreover, the prognostic factors were assessed by Kaplan-Meier analysis and Cox proportional hazards models. Additionally, functional assays were conducted and the potential mechanism was explored. RESULTS: Our study showed that BCAR4 expression was significantly up-regulated in cervical cancer tissue and cell lines. Moreover, patients with high BCAR4 expression showed worse survival outcomes and overexpression of BCAR4 might be an independent prognostic factor in cervical cancer. Furthermore, overexpression of BCAR4 remarkably promoted the proliferation, motility of cervical cancer cells and silencing BCAR4 significantly suppressed the proliferation, migration and invasion of cervical cancer cells. Additionally, overexpression of BCAR4 promoted epithelial-mesenchymal transition (EMT) process and silencing BCAR4 suppressed EMT process in cervical cancer cells. CONCLUSIONS: The results indicated that BCAR4 might play a crucial role in cervical cancer progression and act as an underlying biomarker for the diagnosis and prognosis of cervical cancer. Highlights: BCAR4 expression was up-regulated in cervical cancer tissues and cell lines. Overexpression of BCAR4 might be an independent prognostic factor in cervical cancer. BCAR4 served as oncogenic roles in the regulation of gastric cancer cells migration, invasion and EMT process.